Teachers’ Practices, Interventions, Benefits and Rewards in Teaching Kindergarten Pupils at Villaverde District, Schools Division of Nueva Vizcaya - Mariñas, Mila (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the teaching practices, interventions, benefits, and rewards associated with kindergarten education in Villaverde District, Schools Division of Nueva Vizcaya. Guided by the Input-Process-Output Model, it employed a descriptive survey design involving the public elementary school kindergarten teachers selected through simple random sampling. Data were gathered using a validated two-part survey questionnaire and analyzed through frequency, percentage, and weighted mean. The respondents were all female, predominantly married, 41 years old and above, Teacher III, and experienced educators, with most having earned units toward a master’s degree and received an outstanding performance rating. Professional development participation was concentrated at the school and division levels, with no reported national or international training. Teaching practices were rated very evident, particularly strategies supporting emotional self-regulation, cognitive development, and emotional expression. Teaching interventions were likewise very evident, with repetitive songs, rhymes, routines, early mathematical activities, storytelling, and self-control exercises receiving the highest ratings. Respondents strongly agreed that kindergarten teaching benefits children’s emotional, social, cognitive, physical, literacy, numeracy, and school-readiness development. They also identified strong relationships with pupils and families, children’s learning milestones, and classroom engagement as major professional rewards. Comparatively lower ratings were recorded for promoting self-esteem, helping pupils identify emotions, and some creativity- and critical-thinking interventions. The study concludes that effective kindergarten teaching requires holistic, nurturing, inclusive, and developmentally appropriate practices. It recommends strengthening social-emotional and play-based learning, collaboration with parents and colleagues, purposeful technology use, teacher well-being, continuous professional development, and further research. The study supports SDG 4 on Quality Education, SDG 3 on Good Health and Well-Being, and SDG 10 on Reduced Inequalities. Its sustainability impact lies in strengthening educational quality, institutional support, teacher development, inclusive learning, and sustained school-community involvement in early childhood education.
Keywords: Early Childhood Education; Emotional Development; Kindergarten Teaching; Play-Based Learning; Professional Development; School Readiness; Teaching Interventions; Teaching Practices